VD_FINDINFO Décision / 2016 / 245 vom 12. April 2016 - VD Tribunal cantonal (2016)
DÉTENTIONINCARCÉRATION, RISQUE DE COLLUSION, RISQUE DE RÉCIDIVE, SOUPÇON | 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH)